2011
DOI: 10.5559/di.20.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Attachment to Friends

Abstract: Our study examines the relations of attachment and personality dimensions in young adults. Particular focus of the study is attachment to friends, a form of intimate relations that is less frequently represented in attachment research. For this purpose, modified Brennan's Inventory of Experience in Close Relations (Kamenov & Jelić, 2003) and NEO PI-R assessing five personality dimensions (Costa & McCrae, 1992) were administered to the sample of 352 university students. Results demonstrate a variety of relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
3
8
0
4
Order By: Relevance
“…This may be particularly true in Western societies, where there is a strong emphasis on independence and individuality (Bornstein & Huprich, 2006; Neki, 1976; Tait, 1997). Problematic dependency has been researched and discussed for many years (Fenichel, 1945; Kraepelin, 1913; Schneider, 1923; Sullivan, 1947) and criteria for assessing pathological dependency have been present since the inception of the Diagnostic and Statistical Manual of Mental Disorders (1st ed [DSM‐I]; American Psychiatric Association, 1952).…”
Section: Components Of Do Dd Hdmentioning
confidence: 99%
“…This may be particularly true in Western societies, where there is a strong emphasis on independence and individuality (Bornstein & Huprich, 2006; Neki, 1976; Tait, 1997). Problematic dependency has been researched and discussed for many years (Fenichel, 1945; Kraepelin, 1913; Schneider, 1923; Sullivan, 1947) and criteria for assessing pathological dependency have been present since the inception of the Diagnostic and Statistical Manual of Mental Disorders (1st ed [DSM‐I]; American Psychiatric Association, 1952).…”
Section: Components Of Do Dd Hdmentioning
confidence: 99%
“…McCrae and Costa (1989) showed that the interpersonal circumplex was defined by the two dimensions of Extraversion and Agreeableness. Marušić, Kamenov, and Jelić (2011) found that avoidance in friendships was also characterized by these two personality traits. In a collectivistic culture (Earley, 1989;Kwan, 2009;Tjosvold, Wu, & Chen, 2010), self is not an independent entity and not complete by itself, and is relational and defined by the surrounding personal encounters (G. Gao, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Nesigurna privrženost u romantičnim vezama se nadoknađivala sigurnijom u ostalim, manje ugrožavajućim vezama s prijateljima i članovima obitelji. Nalazi da ljudi mogu imati različite stilove privrženosti tijekom života i u različitim vrstama odnosa bacaju drugačije svijetlo na klasičnu teoriju privrženosti (Marušić, Kamenov i Jelić, 2006). Kasnije je dodatno istraživana privrženost među prijateljima (Marušić, Kamenov i Jelić, 2011;Lotar Rihtarić i Kamenov, 2013 ).…”
Section: Bliski Odnosi Partnerstvo I Privrženostunclassified
“…Nalazi da ljudi mogu imati različite stilove privrženosti tijekom života i u različitim vrstama odnosa bacaju drugačije svijetlo na klasičnu teoriju privrženosti (Marušić, Kamenov i Jelić, 2006). Kasnije je dodatno istraživana privrženost među prijateljima (Marušić, Kamenov i Jelić, 2011;Lotar Rihtarić i Kamenov, 2013 ). Istraživana je i privrženost u bliskim odnosima tijekom različitih životnih razdoblja, tj.…”
Section: Bliski Odnosi Partnerstvo I Privrženostunclassified
See 1 more Smart Citation